2020
DOI: 10.28974/idojaras.2020.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extreme climate conditions on the forest fire risk in the Timočka Krajina region (northeastern Serbia)

Abstract: ⎯ The dependence of the influence of extreme climate conditions on the variability of forest fires in the Timočka Krajina region of northeastern Serbia was studied. The impact of extreme conditions was investigated with extreme climate indices using air temperature, relative humidity, and precipitation measured at three meteorological stations in northeastern Serbia. The De Martonne index was used to analyze climate conditions as a measure for aridity. The study analyzes trends in extreme climate indices with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…On a regional scale, atmospheric circulation determines climatic elements that affect fires, and these are winds, precipitation, relative humidity, soil moisture, and air temperature (Amraoui et al, 2014;Pereira et al, 2005). The most favorable conditions for forest fires in Serbia are high air temperatures, low relative humidity, wind, and lack of precipitation (Tošić et al, 2020;Tošić et al, 2019). Malinovic-Milicevic et al (2016) state that trends in the duration of extreme temperatures and small amounts of precipitation are most pronounced in the summer season.…”
Section: Introductionmentioning
confidence: 99%
“…On a regional scale, atmospheric circulation determines climatic elements that affect fires, and these are winds, precipitation, relative humidity, soil moisture, and air temperature (Amraoui et al, 2014;Pereira et al, 2005). The most favorable conditions for forest fires in Serbia are high air temperatures, low relative humidity, wind, and lack of precipitation (Tošić et al, 2020;Tošić et al, 2019). Malinovic-Milicevic et al (2016) state that trends in the duration of extreme temperatures and small amounts of precipitation are most pronounced in the summer season.…”
Section: Introductionmentioning
confidence: 99%
“…Forest fires occur in Serbia almost every year and are a limiting factor in the sustainable development of forestry [27]. Many studies [4,19,20,26,28,29,30,31] have indicated that there is a correlation between the occurrence of forest fires in Serbia and climate conditions. The distribution of the fire-affected areas and the dynamics of fire outbreaks can be correlated with the climatic characteristics of certain areas [25].…”
Section: Introductionmentioning
confidence: 99%